2020
DOI: 10.1002/aqc.3322
|View full text |Cite
|
Sign up to set email alerts
|

Rescue and relocation of benthic organisms during an urban‐port development project: Port of Manzanillo, case study

Abstract: The present study originated with the expansion of the boardwalk within the urban and port area of Manzanillo, México. Prior to civil works related to the placement of tetrapods, surveys of potential sites for the relocation of benthic organisms in alternative areas were carried out. Based on indicators of the physical–chemical environment and biotic factors, nine areas with potential for relocation were evaluated. The areas of greatest potential were associated with environments located away from the influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The deleterious effect of the presence of C. riisei recorded here in Manzanillo contrasts with what was found on sunken ships in Brazil (de Pádua et al, 2022), where the presence of C. riisei favored the richness of species and abundance of associated communities. In Manzanillo, the higher total species richness on the shipwreck than on the rock, irrespective of C. riisei , suggests that the metallic substrate of the ship has functioned as an artificial reef; some groups of invertebrates have achieved a species richness similar to or even greater than in other areas within the bays of Manzanillo, such as the port area (Liñan‐Rico et al, 2020) or the Carrizales coral reef that is ~8 km away (Alonso‐Domínguez et al, 2022). However, even though the San Luciano sank for more than 50 years, there is no history of inventories of the benthic species associated with it, nor of the temporal changes in the medium or long term in the community structure or information that would date the establishment of C. riisei in this site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The deleterious effect of the presence of C. riisei recorded here in Manzanillo contrasts with what was found on sunken ships in Brazil (de Pádua et al, 2022), where the presence of C. riisei favored the richness of species and abundance of associated communities. In Manzanillo, the higher total species richness on the shipwreck than on the rock, irrespective of C. riisei , suggests that the metallic substrate of the ship has functioned as an artificial reef; some groups of invertebrates have achieved a species richness similar to or even greater than in other areas within the bays of Manzanillo, such as the port area (Liñan‐Rico et al, 2020) or the Carrizales coral reef that is ~8 km away (Alonso‐Domínguez et al, 2022). However, even though the San Luciano sank for more than 50 years, there is no history of inventories of the benthic species associated with it, nor of the temporal changes in the medium or long term in the community structure or information that would date the establishment of C. riisei in this site.…”
Section: Discussionmentioning
confidence: 99%
“…On Colombian reefs, the presence of C. riisei was related to competition for space, which resulted in the overgrowth of Leptogorgia and Pacifigorgia sea fans by C. riisei, causing high mortality in their populations.The deleterious effect of the presence of C. riisei recorded here in Manzanillo contrasts with what was found on sunken ships inBrazil (de Pádua et al, 2022), where the presence of C. riisei favored the richness of species and abundance of associated communities. In Manzanillo, the higher total species richness on the shipwreck than on the rock, irrespective of C. riisei, suggests that the metallic substrate of the ship has functioned as an artificial reef; some groups of invertebrates have achieved a species richness similar to or even greater than in other areas within the bays of Manzanillo, such as the port area(Liñan-Rico et al, 2020) or the Carrizales coral reef that is ~8 km away (Alonso-Domínguez et al, 2022). However, even though the San Luciano sank for more than 50 years, there is no history of inventories of the benthic species associated with it, nor of the temporal changes in the medium or long term in the community structure or information that would date the establishment of C. riisei in this site.The models suggested that in the area with the rocky substrate (San Pedrito) without C. riisei, there may be increases in species richness, diversity of moderately abundant species, and diversity of dominant species, until they surpass those on the San Luciano shipwreck.The heterogeneity and complexity at San Pedrito may provide more environmental niches, and increased sampling effort might reveal a higher species richness.…”
mentioning
confidence: 99%
“…The comprehensive collection, transportation and relocation of benthic communities is a poorly documented topic in the scientific literature (Liñán‐Rico et al . 2020). There have been several coral relocation projects associated with construction of pipelines and they are generally reported in non‐peer reviewed literature (Anonymous 2007; Monkivitch 2008; Seguin et al .…”
Section: Introductionmentioning
confidence: 99%